INNOVATION IN TECHNOLOGY TRANSFER FOR SUSTAINABLE GROWTH IN THE TEACHING AND LEARNING OF ISLAMIC STUDIES IN EKITI STATE, NIGERIA - Yisa Olorunda BALOGUN (CV. ADIBA AISHA AMIRA, 2025)
Driving innovation is an important aspect of a successful teaching and learning in the universities. A lecturer who cannot engage in innovation cannot contribute to a meaningful growth in a given society. The paper examines the aims and objectives of Islamic Studies, the relevance of Islamic Studies in Nigeria, clarification of major concepts, different technological advancements in Nigeria and genesis of Islamic Studies in Ekiti State, Nigeria. Findings reveal that Islamic Studies is facing a lot of challenges in Ekiti State universities in term of low number of lecturers, inadequate instructional materials, enrollment of students and language barrier on the parts of students and lecturers. Our recommendations include constant use of internet to download the latest materials on Islamic Studies, employment of more qualified lecturers to teach Islamic Studies, locally provision of more teaching aids and other instructional materials, and creation of awareness to the parents, guardians and wards on the importance of Islamic Studies and the need to study it.